Pauper Children and Poor Law Childhoods in England and Wales 1834-1910 - Lesley Hulonce (Rounded Globe, 2016)
Poor children in Victorian Britain might be sent to a workhouse, an orphanage, or if they were disabled, a specialist boarding school. Most 'pauper' children however were fostered or remained at home with their families. This is the first full-length book to explore all the options open to Poor Law Unions across England and Wales in their care and treatment of poor children. While we hear regularly about the scandals and abuse that befell vulnerable young people, this book shows how kindness, caring and concern were often shown to these 'Children who belong to the State'. Using autobiographies and memoirs by the children themselves, this book focuses on the child's stories and memories, and by selecting much of the fascinating material from Victorian newspapers, books and records ensures that the reader is kept abreast of the wider historical contexts.